Survival and mortality among users and non-users of hydroxyurea with sickle cell disease - Olinda Maria Rodrigues de Araujo; Maria Lúcia Ivo; Marcos Antonio Ferreira Júnior; Elenir Rose Jardim Cury Pontes; Ieda Maria Gonçalves Pacce Bispo; Eveny Cristine Luna de Oliveira (Universidade de São Paulo, 2015)
OBJECTIVE: to estimate survival, mortality and cause of death among users or not of hydroxyurea with sickle cell disease.METHOD: cohort study with retrospective data collection, from 1980 to 2010 of patients receiving inpatient treatment in two Brazilian public hospitals. The survival probability was determined using the Kaplan-Meier estimator, survival calculations (SPSS version 10.0), comparison between survival curves, using the log rank method. The level of significance was p=0.05.RESULTS: of 63 patients, 87% had sickle cell anemia, with 39 using hydroxyurea, with a mean time of use of the drug of 20.0±10.0 years and a mean dose of 17.37±5.4 to 20.94±7.2 mg/kg/day, raising the fetal hemoglobin. In the comparison between those using hydroxyurea and those not, the survival curve was greater among the users (p=0.014). A total of 10 deaths occurred, with a mean age of 28.1 years old, and with Acute Respiratory Failure as the main cause.CONCLUSION: the survival curve is greater among the users of hydroxyurea. The results indicate the importance of the nurse incorporating therapeutic advances of hydroxyurea in her care actions.